Responses of Processing Tomato Growth and the Soil Microenvironment to Micro‐Nano Aeration and Humic Acid Application Under Warming Drip Irrigation - Chubo Wang; Liang Li; Yongting Zhu; Zhiyu Chai; Qixiang Zhou; Yuhang Lu; Yan Zhu; Libing Song; Jiaying Ma (Irrigation and Drainage, 2026)
Plastic‐mulched drip irrigation is widely used in arid regions, but it may aggravate root‐zone hypoxia and salinity. A two‐year field experiment based on two two‐factor designs was conducted in Xinjiang, China, during 2023 and 2024 to investigate the combined effects of irrigation‐water temperature (10°C–15°C and 20°C–25°C), aeration method (5 mg L −1 (no aeration)) and 18 mg L −1 (micro‐nano aeration) and humic acid application (0 and 0.5% of fertigation mass) on processing tomato growth, yield, fruit quality, root‐zone soil conditions and greenhouse gas fluxes. Micro‐nano aeration and humic acid significantly increased yield and improved fruit quality, with maximum yields of 198.1–205.9 t ha −1 . Irrigation‐water warming increased single fruit weight by 4% and soluble sugar content by 8%–10%. These responses were associated with improved soil oxygen and water availability and reduced effective salinity. Aeration and humic acid increased CO 2 and N 2 O emissions but also promoted CH 4 uptake. Structural equation modelling showed that soil oxygen and temperature were the main drivers of plant growth and lycopene accumulation. The combined application of warmed irrigation water, micro‐nano aeration and humic acid was an effective strategy for improving processing tomato production in arid regions.

Reliability analysis of CRTS III slab ballastless track structure on bridge based on probability density evolution - Li Song; Libing Chen; Maodong Zhu; Wenchang Zhang; Jian Hou (Engineering Structures, 2026)

Treatment of a steroid fermentation residue using ionizing radiation: steroid degradation and biotoxicity abatement - Libing Chu; Yuening Song; Jianlong Wang (Bioresource Technology, 2025)

A NH2-UiO-66-TiO2/Al2O3 hollow ceramic membrane with an enhanced photocatalytic oxidation performance of NO - Wenjuan Yang; Wenli Liu; Yuanbo Song; Yangyang Wang; Yanbin Yun; Guicheng Liu; Chang Li; Jiaming Mao; Jia Liu; Meng Li; Chunyun Zhou; Manxiang Wang; et al. (Journal of Environmental Chemical Engineering, 2025)

Ultra-wide film mulching with moderate irrigation water salinity enhances cotton growth under drip irrigation in Xinjiang, China - Zhanli Ma; Jian Liu; Jinzhu Zhang; Feihu Yin; Li Guo; Yue Wen; Libing Song; Yan Zhu; Yonghui Liang; Zhenhua Wang (Field Crops Research, 2024)

Multi-objective optimization of saline water irrigation in arid oasis regions: Integrating water-saving, salinity control, yield enhancement, and CO2 emission reduction for sustainable cotton production - Zhanli Ma; Yan Zhu; Jian Liu; Yanqiang Li; Jinzhu Zhang; Yue Wen; Libing Song; Yonghui Liang; Zhenhua Wang (Science of The Total Environment, 2024)

Assessing the impact of seasonal freezing and thawing on the soil microbial quality in arid northwest China - Rui Zong; Zhenhua Wang; Wenhao Li; Olusola O. Ayantobo; Haiqiang Li; Libing Song (Science of The Total Environment, 2023)

The Responses of Maize Yield and Water Use to Growth Stage-Based Irrigation on the Loess Plateau in China - Ning Jin; Jianqiang He; Quanxiao Fang; Chao Chen; Qingfu Ren; Liang He; Ning Yao; Libing Song; Qiang Yu (International Journal of Plant Production, 2020)

Correlation between BRAF V600E mutation and clinicopathological features in pediatric papillary thyroid carcinoma - Jiangqiao Geng; Huanmin Wang; Yuanhu Liu; Jun Tai; Yaqiong Jin; Jie Zhang; Lejian He; Libing Fu; Hong Qin; Yingluan Song; Jinzhu Su; Aiying Zhang; et al. (Science China Life Sciences, 2017)

Double-negative feedback loop between ZEB2 and miR-145 regulates epithelial-mesenchymal transition and stem cell properties in prostate cancer cells - Dong Ren; Min Wang; Wei Guo; Shuai Huang; Zeyu Wang; Xiaohui Zhao; Hong Du; Libing Song; Xinsheng Peng (Cell and Tissue Research, 2014)